PEMANFAATAN ABU ROTAN SEBAGAI BAHAN TAMBAH TERHADAP KARAKTERISTIK MARSHALL CAMPURAN ASPAL AC – WC - NAELA HARDIANTI; Hermansyah (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2025)
flexible pavement is a type of pavement that uses asphalt as a binder between the aggregates and has a good level of roughness so that it can be used for high vehicle speeds and has traffic that is not too dense so that it can reduce the maintenance process. One type of mixture in flexible pavement is AC-WC. This research was carried out to determine the effect of adding rattan ash to the AC-WC asphalt mixture by making normal samples and using rattan ash additives with variations of 0.2%, 0.4%, 0.6%, 0.8%. Next, marshall testing and analysis is carried out which includes cavity values, stability, flow and marshall quontient. The results of this analysis were then compared with the AC-WC asphalt mixture reference standard in the 2018 revision 2 specifications. From the results of the research that has been carried out, it can be concluded that the results of using variations of rattan ash will influence the void values ??in the asphalt mixture. From the use of rattan ash variations of 0.2%, 0.4%, 0.6% and 0.8% according to specifications. Of the 4 variations of rattan ash, the variation that got the optimum value was a variation of 0.8%, producing a void value of 4.58%, a void value in the aggregate was 18.35%, a cavity value filled with asphalt was 75.03%, a flow value was 3.60 mm, a marshall stability value of 991 kg, and residual marshall stability was 96.86%.